Purification of rabies virus glycoprotein produced in Drosophila melanogaster S2 cells: An efficient immunoaffinity method - Pilatti, Livia; Mancini Astray, Renato; Rocca, Mayra Pereira [UNESP]; Barbosa, Flavia Ferreira; Jorge, Soraia Attie Calil; Butler, Michael; de Fátima Pires Augusto, Elisabeth (Wiley, 2020)
Most rabies vaccines are based on inactivated virus, which production process demands a high level of biosafety structures. In the past decades, recombinant rabies virus glycoprotein (RVGP) produced in several expression systems has been extensively studied to be used as an alternative vaccine. The immunogenic characteristics of this protein depend on its correct conformation, which is present only after the correct post-translational modifications, typically performed by animal cells. The main challenge of using this protein as a vaccine candidate is to keep its trimeric conformation after the purification process. We describe here a new immunoaffinity chromatography method using a monoclonal antibody for RVGP Site II for purification of recombinant rabies virus glycoprotein expressed on the membrane of Drosophila melanogaster S2 cells. RVGP recovery achieved at least 93%, and characterization analysis showed that the main antigenic proprieties were preserved after purification.
Keywords: Drosophila melanogaster S2 cells; immunoaffinity purification; insect cells; rabies virus glycoprotein